Influence of Burrow Holes in Residual Soil Slope Infiltration - Abu Talib, Zaihasra (International Journal of Integrated Engineering, 2019)
Infiltration rate is important factors in the rainfall induced slope failure. The infiltration of water into residual soil was govern by rainfall intensity and also saturated permeability of soil. The existing of burrow holes has proven increases the permeability of the soil with increase in number of burrow holes. Therefore, it is very important to study the effect of burrow holes in residual soil slope and its effect in infiltration rate. The modified constant head permeability was done to study effect of burrow holes in residual soil. Then, the infiltration test was done to study the infiltration rate of residual soil with existing of burrow holes.Â The result from modified permeability shows that permeability of residual soil increases from 5 x 10-7 m/s to 1.14 x 10-3 m/s for different area of burrow holes. The result from infiltration test proven that when q/ksat greater than 1 the runoff was occurs. Meanwhile, when q/ksat less than 1 infiltration was occurs. The result also indicates that the smaller ratio between of resq/ksat, the faster the infiltration of water into the soil.